THE EFFECT OF MIND MAPPING TECHNIQUE ON THE ABILITY OF THE FIRST GRADE STUDENTS OF SMPN 25 PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Eka Melania Ursula; Fadly Azhar; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is intended to find out whether or not there was a significant effect of Mind Mapping Technique on the ability of the first grade students of SMPN 25 Pekanbaru in comprehending Descriptive Texts. The research design was pre-experimental research with one group pre-test and post-test design. The samples were VII 7 students chosen by using cluster random sampling technique. The Data were calculated by using Microsoft Excel 2010 and analyzed by using SPSS. The result of the data analysis showed that mean score of the pre-test was 59,23 and the mean score of the post-test was 69,32. In other words, the mean score of the post-test was higher than pre-test. The result also showed that the value of t-test (6.648) was higher than t-table (2.024) at significance level of 5%. It can be concluded that Alternative Hypothesis was accepted. Thus, there was a significant effect of Mind Mapping Technique on the ability of the first grade students of SMPN 25 Pekanbaru in comprehending Descriptive Texts. Several recommendations were given for students such as to read more texts, learn to distinguish the important components of the text, learn a lot of material quickly, and share information with their friend in order to get more knowledge and be more focus on increasing their vocabulary. In line with it, the teachers need to give more attention on how to improve students’ comprehension when implementing Mind Mapping in the class.